Comparative Study of Al-Qur'an Memorization Methods at Darul Qur'an and Sulaimaniyah Islamic Boarding Schools in Medan - Syahmira, Pauzia; Hasibuan, Sahdin (Al-Fikru: Jurnal Ilmiah, 2025)
This study is motivated by the challenge of developing effective methods for Al-Qur’an memorization that produce fast and high-quality memorizers. The aim of this research is to compare the Al-Qur’an memorization methods implemented at Pondok Pesantren Darul Qur’an Amplas and Pondok Pesantren Sulaimaniyah Medan. The research adopts a qualitative comparative-descriptive approach, involving teachers, students, and managers selected purposively as subjects. Data was collected through observation, in-depth interviews, and documentation studies, then analyzed through reduction, presentation, and conclusion drawing. The results show that Darul Qur’an uses a tasmi’ and muraja’ah collective method with a completion time of 2.5–3 years, which is effective in building a disciplined character. In contrast, Sulaimaniyah applies the Turkish Utsmani method with a tiered evaluation system that accelerates the achievement of 30 juz in 1–2 years, although it is less flexible for students with low motivation. The implications of this study suggest the need to integrate both methods and adjust the mentoring patterns according to the characteristics of the students to achieve optimal and high-quality memorization results.